Hello all, I'm seeking help in logical equivalence for the following:
{[(p^q)V(p^r)]V(q^r)}^~[(p^q)^r]
It's asking to have an equivalence of that equation using only negations of conditionals(biconditionals too I assume because of the v)
First I take (p∧q), (p∧r), and (q∧r) and (p∧q) which are all conjunctions and change them into the negation of a biconditional based on ^ being the same as <-> which is a conditional so that they are equivalent.
~(p->~q), ~(p->~r), ~(q->~r), ~(p->~q) which gives me the new equation of {[~(p->~q)v~(p->~r)v~(q->~r)]}∧~[~(p->~q)∧r]
I then take the remaining ∧ which are {[~(p->~q)v~(p->~r)v~(q->~r)]}∧~[~(p->~q)∧r] and ~[~(p->~q)∧r and do the same as previously.
I then take the disjunction two at a time starting with ~(p->~q)v~(p->~r) and change it into the negation of a conditional based on v being the same as -> which is a biconditional so that they are equivalent. I am not sure how to do this step.
Afterwards I would take the result of the negation of my conditional which is a biconditional as done above and do it's negation of conditional with the remaining ~(q->~r). I am not sure how to do this step.
I appreciate all the help that i can receive, thank you.
Thank you for any help!